Characterization of bacteria isolates from fermented cassava steeping water - Olalekan Blessing Balogun; Bartholomew Saanu Adeleke; Ibukun Owoseni (International Journal of Applied Biology, 2021)
Cassava is a tuber crop mainly cultivated in Africa countries. The presence of unwanted microorganisms can complicate the control of the fermentation process, which can lead to the production of objectionable odors in steeping water. Microbial and physical analyses during fufu production were performed on the steeping water. Bacteria count decreased with an increase in the fermentation time. The highest bacterial count of 6.6 × 103 CFU/mL, while the least count of 2.2 × 103 CFU/ml was recorded, respectively. The bacteria isolated include Bacillus subtilis, Pseudomonas species, Lactobacillus fermentum, Proteus mirabilis, and Klebsiella sp. The pH value of 3.32 was recorded on day four, while the temperature was constant during the fermentation process. A high value of 45.2 mg/L total solids was recorded on day four, while the least value of 15.0 mg/L was obtained on day one. The effect of fermenting microorganisms under a controlled environment reduces the foul odor usually perceived during fufu production. Hence, the survival of these microorganisms at low pH can inhibit the growth of unwanted microorganisms, thus contributing to the acceptability of the cassava product, i.e. fufu.